The Sanctuary City : Immigrant, Refugee, and Receiving Communities in Postindustrial Philadelphia - Vitiello, Domenic (Book collections on Project MUSE., 2022)
"This book relates the history of Central American, Southeast Asian, Liberian, Arab, and Mexican migration, settlement, and civil society in Philadelphia since the 1970s. It explores the politics of immigration, community relations, and "sanctuary," defined as a wide set of contested protections and assistance at local, national, and transnational scales"--